Vasculitis Following Influenza Vaccination: A Review of the Literature - Watanabe, Toru (Current Rheumatology Reviews, 2017)
Background: Influenza vaccine is safe and effective for the general population as well as for patients with autoimmune diseases. However, although rare, vasculitis has been reported as an adverse event following influenza vaccination. Object: The aims of this literature review were to identify patients who developed vasculitis following influenza vaccination and to clarify the clinical manifestations of vasculitis in these patients. Methods: Using the PubMed database and search engine, we performed a search of the Englishlanguage literature by combining the term influenza vaccination with each term for a specific form of vasculitis from January 1966 through April 2016. Results: A total of 65 patients who developed vasculitis after influenza vaccination were identified from 45 published reports. The majority of patients were elderly, and the patients were predominantly female. The vasculitides included large vessel vasculitis (13 patients), medium vessel vasculitis (2), small vessel vasculitis (42), single organ vasculitis (5), vasculitis associated with systemic disease (1), and vasculitis associated with probable etiology (1). Although the majority of patients achieved complete recovery or remission, there were 3 deaths in patients with ANCA-associated vasculitis and severe long-term sequelae developed in 3 patients (1 with granulomatosis with polyangiitis, 1 with IgA vasculitis and 1 with unclassified small vessel vasculitis). Conclusion: Since vasculitis following influenza vaccination has been only rarely reported, routine influenza vaccination should not be restricted. However, caution should be required when patients with small vessel vasculitis, especially with ANCA-associated vasculitis following influenza vaccination or with post-influenza vaccination-reactivated IgA vasculitis, receive influenza vaccination again.
Keywords: influenza